Internal Ballistics of Recoilless Guns - Ray, Asim (Defence Science Journal, 2014)
A new method for calculating the ballistics of recoilless guns during the period of burning of the propellant has been obtained. Ballistics have also been calculated by exact numerical integration in a few cases and these results have been compared with those obtained by the method described in this paper. It has been found that the results obtained by these two methods agree satisfactorily.